Antimicrobial thermoplastic starch reactive blend with chlorhexidine gluconate and epoxy resin. (1st February 2023) - Thajai, Nanthicha; Rachtanapun, Pornchai; Thanakkasaranee, Sarinthip; Chaiyaso, Thanongsak; Phimolsiripol, Yuthana; Leksawasdi, Noppol; Sommano, Sarana Rose; Sringarm, Korawan; Chaiwarit, Tanpong; Ruksiriwanich, Warintorn; Jantrawut, Pensak; Kodsangma, Araya; et al.
Abstract: An antimicrobial thermoplastic starch (TPS) was developed by melt-mixing TPS with chlorhexidine gluconate (CHG) and epoxy resin (Er). The tensile strength and hardness of the TPSCh blend increased with the addition of Er (TPSCh/Er), especially at 5 wt% Er (TPSCh/Er5) (19.5 MPa and 95 %, respectively). The water contact angle of TPSCh/Er was higher than those of TPS and TPSCh because of the improved interfacial tension. Fourier transform infrared and nuclear magnetic resonance analyses confirmed the reaction between the epoxy groups of Er, hydroxyl groups of starch, and amino groups of CHG. TPSCh/Er5 exhibited a significantly lower CHG release than TPSCh owing to the rearrangement of TPSCh chains via Er crosslinking. TPSCh/Er0.5 and TPSCh/Er1 showed inhibition zones against both tested bacteria ( Staphylococcus aureus and Bacillus cereus ), whereas TPSCh/Er2.5, TPSCh/Er5, and TPSCh/Er10 showed inhibition zones only against S. aureus . Moreover, TPSCh and TPSCh/Er0.5–2.5 exhibited inhibition zones with Saccharomyces cerevisiae . Highlights: Novel thermoplastic starch (TPS) with excellent properties was developed. TPS was blended with chlorhexidine gluconate (CHG) and Epoxy resin (Er). Er 5 % improved high tensile strength (19.5 MPa) of TPS/CHG blend (TPSCh). Epoxy groups of Er effectively reacted with NH groups of CHG in the TPSCh. This reaction provided water resistance, slow release, and antimicrobial properties.